PENGARUH VARIASI KONSENTRASI AVICEL PH 101 DAN LAKTOSA SEBAGAI HOST DALAM PEMBUATAN TABLET CAMPURAN INTERAKTIF GLIMEPIRID MENGGUNAKAN METODE KEMPA LANGSUNG - Muhammad Agung Nugroho; Ilham Kuncahyo; Reslely Harjanti (Jurnal Farmasi & Sains Indonesia, 2025)
Glimepirid is an antidiabetic drug from the sulfonylurea class with low solubility, thus requiring a formulation approach to improve its bioavailability. This study aimed to examine the effect of varying concentrations of avicel pH 101 and lactose as carrier (host) materials on the physical properties and dissolution profile of glimepirid tablets prepared using the direct compression method. Three formulas were developed with avicel pH 101:lactose ratios: F1 (1:0.5), F2 (1:1), and F3 (1.5:1). Quality evaluation included tests of granule flow properties (angle of repose and flow time) and physical tablet tests (content uniformity, hardness, friability, disintegration time, and dissolution) based on the Indonesian Pharmacopoeia. ANOVA statistical analysis showed significant differences between formulas (p < 0.05). The results indicated that variations in avicel pH 101 and lactose concentrations affected the physical quality and dissolution profile of the tablets. Formula 1 had the fastest disintegration time and the highest drug release. Formula 2 demonstrated the best content uniformity, good powder flow, and stable dissolution. Formula 3 produced the hardest tablets with the lowest friability but required longer disintegration time. Formula 2 was considered the most optimal and is recommended for further development of glimepirid tablets.